Characterization of osteoblastic and osteolytic proteins in prostate cancer bone metastases1. Issue 9 (17th January 2013) - Larson, Sandy R.; Zhang, Xiaotun; Dumpit, Ruth; Coleman, Ilsa; Lakely, Bryce; Roudier, Martine; Higano, Celestia S.; True, Lawrence D.; Lange, Paul H.; Montgomery, Bruce; Corey, Eva; Nelson, Peter S.; et al.
Abstract BACKGROUND Approximately 90% of patients who die of Prostate Cancer (PCa) have bone metastases, which promote a spectrum of osteoblastic, osteolytic or mixed bone responses. Numerous secreted proteins have been reported to promote osteoblastic or osteolytic bone responses. We determined whether previously identified and/or novel proteins were associated with the osteoblastic or osteolytic response in clinical specimens of PCa bone metastases. METHODS Gene expression was analyzed on 14 PCa metastases from 11 patients by microarray profiling and qRT‐PCR, and protein expression was analyzed on 33 PCa metastases from 30 patients by immunohistochemistry on highly osteoblastic and highly osteolytic bone specimens. RESULTS Transcript and protein levels of BMP‐2, BMP‐7, DKK‐1, ET‐1, and Sclerostin were not significantly different between osteoblastic and osteolytic metastases. However, levels of OPG, PGK1, and Substance P proteins were increased in osteoblastic samples. In addition, Emu1, MMP‐12, and sFRP‐1 were proteins identified with a novel role of being associated with either the osteoblastic or osteolytic bone response. CONCLUSIONS This is the first detailed analysis of bone remodeling proteins in human specimens of PCa bone metastases. Three proteins not previously shown to be involved may have a role in the PCa bone response. Furthermore, our data suggests that the relative expression of numerous, rather than a single, bone remodeling proteins determine the bone response in PCa bone metastases. Prostate 73: 932–940, 2013. © 2013 Wiley Periodicals, Inc.